Protecting the Freedom to Read in Maine - Durney, Sonya (Maine Policy Review, 2024)
The freedom to read is essential to our democracy and supports an informed citizenry, yet it faces continuous threats. This article examines the historical and contemporary challenges to this freedom. It discusses the resurgence of book bans, the motivations behind these efforts, and the responses from various stakeholders. By highlighting recent trends and legislative actions, the article aims to inform policymakers and concerned citizens about the importance of protecting the right to read in Maine libraries.